Issues for Today : Reading For Today SERIES, BOOK 3 - Smith, Lorraine C.; Mare, Nancy Nici (Thomson Heinle, 2004)
These best-selling, academic skills books systematically develop reading and vocabulary skills through engaging themes and intensive practice. Readers learn successful reading strategies and are further prompted to build proficiency in their writing, listening, and speaking skills.